2011
DOI: 10.1016/j.gaceta.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Hombres jóvenes que tienen sexo con hombres: ¿un colectivo en alto riesgo para la infección por el VIH?

Abstract: YMSM do not constitute a group at increased risk of HIV/STI infection compared with respondents >25 years old. However, there are some variables could contribute to vulnerability in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…This situation has contributed to a dramatic rise in the prevalence of STIs in the youth and adult population. Other practices that could explain this situation are oral and anal sex [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…This situation has contributed to a dramatic rise in the prevalence of STIs in the youth and adult population. Other practices that could explain this situation are oral and anal sex [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…The profile of people who did not know their HIV status before diagnosis were patients younger than 25 years or those older than 44 years and who had heterosexual sex (7,8) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Numerous studies developed in Spain have shown a high frequency of sexual risk behaviors among young heterosexuals and homosexuals (9)(10)(11)(12)(13)(14)(15), but few studies have examined the frequency of HIV antibody testing and determinants of delayed diagnosis (16). According to the Survey on Health and Sexual Habits conducted by the National Statistics Institute, only 10.4 % of the population in Spain has been tested voluntarily to find out their HIV status (17).…”
mentioning
confidence: 99%
“…We have explored a specific practice, namely online cruising among young men who have sex with men. We have thus responded to an explicit concern in epidemiology, namely the persistence of sexually transmitted infections, in-cluding HIV, as health problems in young men 5 .…”
Section: Discussionmentioning
confidence: 99%
“…MSM who cruise for partners on the Internet report having more encounters without condoms when compared to other MSM 4 . In Spain, young MSM are more likely to practice unsafe sex (73% ≤ 25 years of age versus 57% > 25 years) 5 .…”
Section: Background and Objectivesmentioning
confidence: 99%